Ferroelectric BaTaO2N perovskite — Towards structure-property relationship study on high-quality crystals and ceramics prepared with the aid of liquid phase - Hosono, Akira; Masubuchi, Yuji; Higuchi, Mikio; Kikkawa, Shinichi (Solid state sciences, 2023)
The ternary metal oxynitride compound, perovskite-type BaTaO2N, has been a subject of interest for solid-state physicists and chemists. The notable dielectric property has been reported in a centrosymmetric average structure although the anisotropic anion configuration is preferable in cis-TaO4N2 octahedra around Ta5+ with d0 electron state. Either single crystals or sintered ceramics in high quality is necessary to clarify the puzzle between the structure and property. Thin film studies are sometimes misleading and confusing. This report reviews the preparation of BaTaO2N in high quality from the viewpoints of its crystal growth in a liquid phase, sintering in a thick ceramic form, and low-temperature and short time sintering with a liquid phase additive to obtain the high-quality samples for investigation of the structure-dielectric property relationship. [Display omitted] •Research history of the crystal growth and sintering of BaTaO2N ferroelectrics was reviewed.•Single crystal of BaTaO2N was obtained in BaCN2 flux and showed clear evidence of ferroelectricity.•Dense ceramic thick film of BaTaO2N was obtained by high-temperature liquid-phase sintering and annealing.•Low-temperature sintering using BaCN2 melt formed BaTaO2N ceramic products without nitrogen loss.